Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Dinas Lingkungan Hidup Provinsi DKI Jakarta - Hajjatul Alfina Putri; Diana Tambunan (CV. ITTC INDONESIA, 2025)
The Environmental Agency of DKI Jakarta Province is a government institution engaged in the field of environmental protection and management, including cleanliness and waste management. This agency plays a significant role in planning and is responsible for environmental planning, environmental impact assessment, supervision of business activities affecting the environment, and providing public services related to the environment. This study aims to analyze and determine the influence of Work Motivation and Work Discipline on Employee Performance at the Environmental Agency of DKI Jakarta Province. This research utilized a questionnaire distributed to employees in the general section of the agency. The collected data from the questionnaires were tabulated and subsequently processed using SPSS version 27. The results of this study indicate that Work Motivation has a significant effect on employee performance at the Environmental Agency of DKI Jakarta Province, Work Discipline also significantly affects employee performance, and both Work Motivation and Work Discipline simultaneously have a significant influence on employee performance.